2018
DOI: 10.12691/jfnr-6-7-7
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of Eating Disorders, Nutritional and Health Status Based on Eating Attitude Test-26 amongst University Adolescent Girls

Abstract: Eating disorder causes serious disturbances in behaviors related to nutrition in adolescent. Although most of these attitudes are benign, they can bear significant psychological and health risks. A cross-sectional study was conducted on 250 university adolescent girls studying in Peshawar Pakistan to explore their eating disorder, nutritional and health status. Girls were interviewed for eating attitudes by using Eating Attitude Test (EAT-26), socio-economic status and body image. Anthropometric and biochemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…Body size misperceptions in young adult females were found to be positively correlated with the development of eating disorder symptoms such as dieting, excessively restricting, and limiting the quantity and types of food consumed, denying feeling hungry, and avoiding certain foods [14]. This unhealthy dietary habit could result in deficiency of various essential nutrients as well as the development of nutritional diseases such as anemia, particularly IDA [43]. Accordingly, an inverse correlation was found between anemia development and women BMI values in Jordan [44].…”
Section: Discussionmentioning
confidence: 99%
“…Body size misperceptions in young adult females were found to be positively correlated with the development of eating disorder symptoms such as dieting, excessively restricting, and limiting the quantity and types of food consumed, denying feeling hungry, and avoiding certain foods [14]. This unhealthy dietary habit could result in deficiency of various essential nutrients as well as the development of nutritional diseases such as anemia, particularly IDA [43]. Accordingly, an inverse correlation was found between anemia development and women BMI values in Jordan [44].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence scores from our study (13.90% with high score in EAT-26) are higher than this report. Another study (Syed et al, 2018) conducted on 250 adolescent college students in Pakistan found that 29.2% of young girls had EAT-26 scores of 20 or higher.…”
Section: Discussionmentioning
confidence: 99%
“…Analisis menunjukkan bahwa risiko gangguan makan tidak memiliki hubungan yang bermakna dengan anemia. Hal ini sejalan dengan penelitian yang dilakukan pada remaja yang menemukan tidak adanya hubungan antara eating disorder dengan status anemia (Syed et al, 2018). Penelitian lain yang dilakukan di Bekasi memperlihatkan hasil yang sama dimana risiko gangguan makan tidak berhubungan dengan anemia pada remaja putri (Syah & Asna, 2018).…”
Section: Pembahasanunclassified